A critical review on Tomato leaf curl virus resistance in tomato. Issue 4 (4th July 2019) - Singh, Ramesh Kumar; Rai, Nagendra; Singh, Amareesh Kumar; Kumar, Prashant; Singh, Bijendra
ABSTRACT: Tomato leaf curl virus (ToLCV) causes a disease of tomato ( Solanum lycopersicum L.) worldwide and jeopardizes sustainable production, with yield losses up to 100%. The Tomato leaf curl disease in the Varanasi region of India is caused by Tomato leaf curl Gujarat virus (TLCGV). The ToLC disease occurrence is shifting from the rainy to the winter season that may be due to changing climate. A number of resistant genes have been identified in the wild background and a limited number of genotypes resistant to ToLCV are available in tomato. The wild species have been determined to be ToLCV resistant using morphological, biochemical and molecular markers. Tomato populations (F2, F3, Recombinant Inbred Lines) developed using wild species have been investigated using Mendelian genetics through breeding. Molecular approaches have provided opportunities in the form of linked molecular markers and loci on chromosomes to speed up, and simplify, selection of host resistance genes. However, transformation of resistant genes by genetic engineering is preferred for developing ToLCV resistant varieties. Modern techniques combined with conventional techniques offer opportunities for improving ToLCV resistance in tomato.